Influence of membrane anchoring and cytoplasmic domains on the fusogenic activity of vesicular stomatitis virus glycoprotein G. - Odell, D (1997)
Chimeric proteins in which the transmembrane anchoring sequence (TM) or both the TM and the cytoplasmic tail (CT) of vesicular stomatitis virus glycoprotein G were replaced with corresponding domains of viral or cellular integral membrane proteins were used to examine the influence of these domains on acidic-pH-induced membrane fusion by G protein. The TM and CT of G were also replaced with the lipid anchor glycosylphosphatidylinositol. Hybrids containing foreign TM or TM and CT sequences were fusogenic at acidic pH but glycosylphosphatidylinositol-anchored G was nonfusogenic at acidic pH. The results suggest that the fusogenic activity of G protein requires membrane anchoring by a hydrophobic peptide sequence and the specific amino acid sequence of the TM has no influence on fusogenic activity.